Development of Physics Learning Modules Integrated with Wonosobo Local Wisdom on Temperature and Heat Materials to Overcome Student Misconceptions - nurjannah, farah afika; Majid, Abdul; Firdaus, Firdaus (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This study aims to: (1) Know the level of validity of the Wonosobo local wisdom integrated learning module so that it is feasible to be used to overcome students' misconceptions. (2) To know the level of practicality of the learning module integrated with local wisdom Wonosobo to overcome students' misconceptions. (3) To determine the effectiveness of the learning module integrated with local wisdom Wonosobo to overcome students' misconceptions. The subjects in this study were students of SMA Takhassus Al Qur'an class XI MIPA 5 totaling 20 students. The research used the R & D method with the Borg & Gall development model. The data analysis technique used is quantitative and quantitative analysis. The results of the development of this learning module show that the results of material validity obtained an average score of 3.39 on a scale of 4 or 85.1% while the results of media validity obtained an average score of 3.69 on a scale of 4 or 93.35% so that the module developed is included in the valid category. The results of the analysis resulted in t count> from t table where t count is below the Ha acceptance area. The result of an increase of 0.4 or 8% of the increase is not enough, but it is effective enough to overcome misconceptions. The results of the assessment of participants obtained an average score of 14.7 or 90.7% so it is in the very practical category.